Endomembrane Ca2+-ATPases play a significant role in virus-induced adaptation to oxidative stress - Shabala, Sergey; Bækgaard, Lone; Shabala, Lana; Fuglsang, Anja T.; Cuin, Tracey Ann; Nemchinov, Lev G.; Palmgren, Michael G. (Plant signaling & behavior, 2011)
Although the role of Ca 2+ influx channels in oxidative stress signaling and cross-tolerance in plants is well established, little is known about the role of active Ca 2+ efflux systems in this process. In our recent paper, 17 we reported Potato Virus X (PVX)-induced acquired resistance to oxidative stress in Nicotiana benthamiana and showed the critical role of plasma membrane Ca 2+ /H + exchangers in this process. The current study continues this research. Using biochemical and electrophysiological approaches, we reveal that both endomembrane P 2A and P 2B Ca 2+ -ATPases play significant roles in adaptive responses to oxidative stress by removing excessive Ca 2+ from the cytosol, and that their functional expression is significantly altered in PVX-inoculated plants. These findings highlight the crucial role of Ca 2+ efflux systems in acquired tolerance to oxidative stress and open up prospects for practical applications in agriculture, after in-depth comprehension of the fundamental mechanisms involved in common responses to environmental factors at the genomic, cellular and organismal levels.